2017
DOI: 10.1097/scs.0000000000002830
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Different Forms and Involved Bones of Craniofacial Fibrous Dysplasia

Abstract: This meta-analysis found that monostotic and polyostotic forms of CFD shared similar prevalence rates. Furthermore, the maxilla was found to be the most commonly involved bone in both monostotic and polyostotic CFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
0
24
0
4
Order By: Relevance
“…Additionally, patients who are diagnosed with "monostotic" FD may not be appropriately evaluated for polyostotic and endocrine disease, making it difficult to determine the relative prevalence of these subtypes. A metanalysis of 18 series including a total of 487 patients diagnosed with craniofacial FD reported that 56% had monostotic disease, 47% had polyostotic disease, and 7% had MAS [2]. It is unclear whether these patients were screened for subclinical endocrine disease, calling into question the generalizability of these findings.…”
Section: Epidemiologymentioning
confidence: 99%
“…Additionally, patients who are diagnosed with "monostotic" FD may not be appropriately evaluated for polyostotic and endocrine disease, making it difficult to determine the relative prevalence of these subtypes. A metanalysis of 18 series including a total of 487 patients diagnosed with craniofacial FD reported that 56% had monostotic disease, 47% had polyostotic disease, and 7% had MAS [2]. It is unclear whether these patients were screened for subclinical endocrine disease, calling into question the generalizability of these findings.…”
Section: Epidemiologymentioning
confidence: 99%
“…The long delay of the clinical management of the patient's disease would probably responsible for her considerable craniofacial deformation. The maxillary bone was described in the literature as the main site of malignant transformation, followed by the mandible, and zygoma in the case of aggressive dysplasia, [3,4].…”
Section: Epidemiological and Clinical Characteristics Of Aggressive Cmentioning
confidence: 99%
“…The McCune-Albright syndrome is a rare disease characterized by skeletal lesions, skin hyperpigmentations, and hyperfunctional endocrinopathies. It represents less than 7 % of bone dysplasia and its prevalence is estimated at between 1/100,000 and 1/1,000,000 [3,4]. It slowly evolves but might be aggressive in exceptional cases or lead to malignant transformation in 0.9-4% of cases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of FD of the temporal bone (FDTB) is variable and accounts for up to 89% of craniofacial FD, 2 but only 12% of isolated FDTB. 3 Patients with FD usually present with headache, pain, sensory deficit, functional impairment, and infectious complications. 4 The most common presenting complaint of FDTB is hearing loss (58%) 5 and is usually conductive.…”
Section: Introductionmentioning
confidence: 99%